2004
DOI: 10.1016/j.jacc.2003.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin dose and six-month outcome after an acute coronary syndrome

Abstract: Although these data are non-randomized, they suggest that the aspirin dose upon discharge may influence the clinical course after unstable angina or acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Indeed, there is evidence to suggest that response to low-dose aspirin varies with anatomic distribution of atherothrombosis. 48 Secondary prevention studies in large populations, however, fail to show additional clinical benefit of higher aspirin doses. 23 Indeed, evidence that gastrointestinal injury increases as aspirin dose exceeds the dosage required for an antiplatelet effect, as well as the increasing prescription of combined antiplatelet therapy, may underlie the recent downward revision of recommended aspirin maintenance doses in patients with CAD.…”
Section: Aspirin Dosementioning
confidence: 99%
“…Indeed, there is evidence to suggest that response to low-dose aspirin varies with anatomic distribution of atherothrombosis. 48 Secondary prevention studies in large populations, however, fail to show additional clinical benefit of higher aspirin doses. 23 Indeed, evidence that gastrointestinal injury increases as aspirin dose exceeds the dosage required for an antiplatelet effect, as well as the increasing prescription of combined antiplatelet therapy, may underlie the recent downward revision of recommended aspirin maintenance doses in patients with CAD.…”
Section: Aspirin Dosementioning
confidence: 99%
“…11 Multiple other studies have shown that aspirin doses ranging from 30 to 325 mg show a differential increase in GI bleeding as aspirin dose is increased. [12][13][14] The differential GI bleeding with dose is consistent with the differential suppression of COX-I with dose. This does not include the slight increased risk of hemorrhagic stroke of 0.2 events per 1,000 patient-years of aspirin therapy.…”
mentioning
confidence: 69%
“…Propensity score analysis has been used successfully to compare different treatment options in a nonrandomized design [23]. The strength and direction of association favoring early IIT was consistent after propensity score modeling regardless of method used for analysis (OR 0.16-0.31).…”
Section: Discussionmentioning
confidence: 95%
“…This has been used successfully to compare different treatment options in observational studies to minimize the effects of confounding by indication [23][24][25]. Propensity score for early vs. late administration of insulin was calculated for all patients.…”
Section: Discussionmentioning
confidence: 99%